How should MDG implementation be measured: Faster progress or meeting targets? - Sakiko Fukuda-Parr; Joshua Greenstein (International Policy Centre for Inclusive Growth (IPC-IG), 2010)
This paper questions the methodology that is widely used to assess progress in implementing the Millennium Development Goals (MDGs), a methodology that asks whether the targets are likely to be met. This approach is inappropriate, since the MDGs were neither designed as nor intended to be planning targets. They were political commitments, made by world leaders, that define priorities in a normative framework and that can be used as benchmarks in evaluating progress. In this framework the appropriate question is whether more is being done to live up to that commitment, resulting in faster progress. We present a methodology and analysis using this new framework, and find that our assessment of progress differs considerably from that arising from the conventional methodology. For example, while access to safe water is touted as an MDG success, only a third of the countries improved at a faster rate. Overall, in most indicators and in most countries, progress has not accelerated.
Keywords: 330; Millennium Development Goals; Wirkungsanalyse